PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERORIENTASI LIFE SKILLS MEMANFAATKAN BAHAN BAKU KEDELAI LOKAL (Journal of Innovative Science Education, 2012)
Abstract Learning device create well-order stage in the process of learning in school. Graduate students of high school lacked of life skills, so that they possessed the same ability as a vocational school graduates. The purpose of this research was to develop the life skills-oriented biology learning device by utilizing soybean as the local raw material, affect the learning outcomes, know students’ and teachers response. This research modified the Model of Thiagarajan, Semmel & Semmel. The tested on a small scale of grade X cinsisted of 34 students. The implemented on a large-scale in three schools are the accredited school, SSN, and RSBI.The results showed that there was no development of life skills-oriented learning device in the school. For developing the life skills-oriented biology learning device by utilizing soybean as the local raw material, the writer maximized it as an indicator with the achievement of Competency Standard (KD) and associated with soybean-producing areas. The development of learning device had a significant effect on learning outcomes of student. T test for both mean difference indicated a t-value = 3.35 ≥ t-table = 2.92. While the students and teachers gave positive responses. Abstrak Perangkat pembelajaran menciptakan keteraturan tahapan dalam proses pembelajaran yang berlangsung di sekolah. Lulusan SMA kurang memiliki kecakapan hidup (life skills) seperti lulusan sekolah kejuruan. Tujuan dari penelitian ini adalah mengembangkan perangkat pembelajaran biologi yang berorientasi life skills dengan memanfaatkan bahan baku kedelai lokal, pengaruhnya terhadap hasil belajar, respon peserta didik dan guru. Penelitian ini memodifikasi Model Thiagarajan, Semmel & Semmel. Uji coba pada skala kecil kelas X sejumlah 34 peserta didik. Pada skala besar dengan implementasi di 3 sekolah yaitu sekolah Terakreditasi, SSN, dan RSBI. Hasil penelitian menunjukkan bahwa belum ada pengembangan perangkat pembelajaran berorientasi life skills. Untuk pengembangan perangkat pembelajaran biologi berorientasi life skills dengan pemanfaatan bahan baku kedelai lokal, pengembangannya dengan memaksimalkan indikator pencapaian dari Standar Kompetensi (KD) dikaitkan dengan daerah penghasil kedelai. Pengembangan perangkat pembelajaran berpengaruh signifikan terhadap hasil belajar. Uji t untuk perbedaan kedua rerata ini menunjukkan nilai t-hitung = 3,35 ≥ t-tabel = 2,92. Sedangkan peserta didik dan guru memberikan respon positif.